Tumor-induced pressure in the bone microenvironment causes osteocytes to promote the growth of prostate cancer bone metastases - Sottnik, Joseph L. (Cancer Res, 2015)
Crosstalk between tumor cells and their microenvironment is critical for malignant progression. Crosstalk mediators including soluble factors and direct cell contact have been identified, but roles for the interaction of physical forces between tumor cells and the bone microenvironment have not been described. Here we report preclinical evidence that tumor-generated pressure acts to modify the bone microenvironment to promote the growth of prostate cancer bone metastases. Tumors growing in mouse tibiae increased intraosseous pressure. Application of pressure to osteocytes, the main mechanotransducing cells in bone, induced PCa growth and invasion. Mechanistic investigations revealed that this process was mediated in part by upregulation of CCL5 and matrix metalloproteinases in osteocytes. Our results defined the critical contribution of physical forces to tumor cell growth in the tumor microenvironment, and they identified osteocytes as a critical mediator in the bone metastatic niche.